2023
DOI: 10.3389/fimmu.2023.1071580
|View full text |Cite
|
Sign up to set email alerts
|

Mendelian randomization study shows a causal effect of asthma on epilepsy risk

Abstract: ObjectiveThe relationship between asthma and epilepsy in observational studies is controversial. The purpose of this Mendelian randomization (MR) study is to investigate whether asthma causally contributes to epilepsy susceptibility.MethodsIndependent genetic variants strongly (P<5E-08) associated with asthma were from a recent meta-analysis of genome-wide association studies on 408,442 participants. Two independent summary statistics of epilepsy obtained from the International League Against Epilepsy C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…(19) A recent cohort study including 150,827 patients with asthma showed that the probability of developing epilepsy in patients with asthma was 1.39 times higher than in healthy controls. (11) In a Mendelian randomization (MR) study whether asthma causally contributes to epilepsy susceptibility was investigated and they reported asthma is associated with an increased risk of epilepsy independent of the age onset of asthma (20). The potential reasons for the association between asthma and epilepsy could be due to anoxia and hypocapnia caused by frequent asthma attacks, or perhaps chronic inflammation is a common pathological feature of asthma and epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…(19) A recent cohort study including 150,827 patients with asthma showed that the probability of developing epilepsy in patients with asthma was 1.39 times higher than in healthy controls. (11) In a Mendelian randomization (MR) study whether asthma causally contributes to epilepsy susceptibility was investigated and they reported asthma is associated with an increased risk of epilepsy independent of the age onset of asthma (20). The potential reasons for the association between asthma and epilepsy could be due to anoxia and hypocapnia caused by frequent asthma attacks, or perhaps chronic inflammation is a common pathological feature of asthma and epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…When I 2 <40%, the heterogeneity of results was not significant, while when I 2 >75%, the heterogeneity of results was significant. A random effects model was used when the heterogeneity of results was significant (I^ 2 ≥50%, or p<0.05), and a common effect model was used when it was not significant (I^ 2 <50% and p≥0.05) ( 24 , 37 , 38 ). Since two-way MR analysis was performed between each cytokine and OLP in this study, we used Bonferroni Hochberg correction, i.e., when p<0.00038 (0.05/132), it suggested that the analysis results were significant.…”
Section: Methodsmentioning
confidence: 99%
“…To eliminate possible linkage disequilibrium (LD), the significantly related SNPs we screened should satisfy both r 2 <0.01, and KB>500. In addition, palindromic SNPs containing ambiguous linkages should also be corrected or excluded (21)(22)(23)(24). We uploaded the screened SNPs to the PhenoScanner website (http:// www.phenoscanner.medschl.cam.ac.uk/) to eliminate confounders associated with the outcome.…”
Section: Selection Of Ivsmentioning
confidence: 99%
“…For IBD, the data were screened and analyzed to enhance the reliability of the results ( P < 5 × 10 –8 ) by referring to multiple publications and developing stricter criteria. [37,38] Meanwhile, we calculated the proportion of phenotypic variation explained and F-statistics for each IV to assess IV strength and avoid weak instrument bias. After removing IVs with low F-statistics (<10), 21 IVs of IBD were retained for further analysis.…”
Section: Methodsmentioning
confidence: 99%